Telomere length correlates with histopathogenesis according to the germinal center in mature B-cell lymphoproliferative disorders - Ladetto, Marco; Compagno, Mara; Ricca, Irene; Pagano, Marco; Rocci, Alberto; Astolfi, Monica; Drandi, Daniela; di Celle, Paola Francia; Dell’Aquila, Maria; Mantoan, Barbara; Vallet, Sonia; Pagliano, Gloria; et al. (Blood, 2004)
In this study we investigated telomere restriction fragment (TRF) length in a panel of mature B-cell lymphoproliferative disorders (MBCLDs) and correlated this parameter with histology and histopathogenesis in relation to the germinal center (GC). We assessed 123 MBCLD samples containing 80% or more tumor cells. TRF length was evaluated by Southern blot analysis using a chemiluminescence-based assay. GC status was assessed through screening for stable and ongoing somatic mutations within the immunoglobulin heavy-chain genes. Median TRF length was 6170 bp (range, 1896-11 200 bp) and did not correlate with patient age or sex. TRF length was greater in diffuse large cell lymphoma, Burkitt lymphoma, and follicular lymphoma (medians: 7789 bp, 9471 bp, and 7383 bp, respectively) than in mantle cell lymphoma and chronic lymphocytic leukemia (medians: 3582 bp and 4346 bp, respectively). GC-derived MBCLDs had the longest telomeres, whereas those arising from GC-inexperienced cells had the shortest (P < 10-9). We conclude that (1) TRF length in MBCLD is highly heterogeneous; (2) GC-derived tumors have long telomeres, suggesting that minimal telomere erosion occurs during GC-derived lymphomagenesis; and (3) the short TRF lengths of GC-inexperienced MBCLDs indicates that these neoplasms are good candidates for treatment with telomerase inhibitors, a class of molecules currently the subject of extensive preclinical evaluation. (Blood. 2004;103:4644-4649)